Strategi Pola Asuh Orang Tua: Studi Kasus Orang Tua Banyak Anak di Dusun Taman Baru Banyuwangi - Muhammad Sofyan; Muhammad Taqy Al-Farras; Muhamad Ridwan Arif; Alfisyah Nurhayati (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This research is entitled "parental parenting strategies: a case study of parents with many children in Taman Baru Banyuwangi hamlet". This research aims to find out how parenting patterns are applied by parents who have many children and researchers chose four parents in this study. This research uses a qualitative research method with a case study approach, using interview and observation instruments in data collection. The results of the research revealed the parenting style provided by each parent, each parent has their own choice in conveying this parenting style to their children and of course they have a purpose for using this parenting style and with the parents' consideration and vigilance. They will definitely be faced with several obstacles because it is not easy to take care of children. And when parents have many children, they certainly have their own way of guiding and paying attention to their children's personalities and daily lives. Because parents definitely want the best for their children both in their educational environment, their relationships and their daily activities. Each parent has their own strategy in determining their parenting style towards their children. Descriptive parenting, authoritarian parenting, and permissive parenting are various parenting patterns, but it is attention and affection that determines a child's personality. Parenting is just a tool to educate children from an early age until they grow up so that they don't lose their personality and identity when they socialize in society.